The effects of social infrastructure and gender equality on output and employment: The case of South Korea. (October 2022) - Oyvat, Cem; Onaran, Özlem
Highlights: We examine the impact of social infrastructure, defined as expenditure in education, childcare, health and social care. Higher social infrastructure expenditure increases female employment more than male employment in the short run. Higher social expenditures raise both male and female employment in the medium run due to increasing output . South Korean economy is gender equality-led, although the impact of gender pay gaps on growth is relatively small. Sustainable equitable development requires a mix of both labour market and fiscal policies. Abstract: This paper examines the short-run and medium-run impact of spending in social infrastructure, defined as expenditure in education, childcare, health and social care, wages and gender pay gap on output and employment of men and women for the case of South Korea. Based on a gendered post-Kaleckian feminist macroeconomic theoretical model, we estimate the macroeconomic effects of social expenditure, wages and gender pay gap using a structural vector autoregression (SVAR) analysis for the period of 1970–2012. The results show that an increase in the public social infrastructure significantly increases the total non-agricultural output and employment in South Korea both in the short and medium run. Moreover, we find that higher social infrastructure expenditure increases female employment more than male employment in the short run and raises both male and female employment in the medium run due to increasing output. Finally, the results show that South Korean economy is gender equality-led in the medium run, although the effects are economically small in comparison to the strong effects of increases social infrastructure spending. The results indicate that sustainable equitable development and a substantial increase in employment requires a mix of both labour market and fiscal policies.